Prognostic Significance of ALT/AST in diabetic patients having Myocarditis secondary to COVID Pneumonia - Muhammad Rashid Ali, Maryam Haroon, Rumla Samayyah, Fareeha Salman, Ambreen Butt, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the predictive accuracy of raised ALT/AST ratio in diabetic patients for survival and myocarditis due to COVID-19 pneumonia. Study design: It was a cross-sectional study, conducted at Department of Medicine, Services Hospital, Lahore for about 6 months (March 2020 to September 2020) Methods: A cross-sectional study was conducted for six months at Services Hospital in Lahore (March 2020 to September 2020). A total of 350 patients’ ALT and AST levels will be tested in blood. Patients’ survival rates will be tracked. Patients with myocarditis and ALT/AST ratios below 0.90 had a dismal prognosis. Results: The average female age was 47.87.15.82. There were 142 men (40%) and 208 women (59.4%). There were 131 light (36.4%), 77 moderate (22%), 83 severe (23.7%), and 59 serious cases (16.9%). Mean ALT/AST was 0.89 0.33. 58 patients (16.6%) had myocarditis, and 66 (18.9%) died in the hospital. Sensitivity, specificity, PPV, NPV, and diagnostic accuracy of the ALT/AST ratio for predicting diabetic patient survival were 56.1%, 39.1%, 17.6%, 79.3%, and 42.3%. The ALT/AST ratio’s sensitivity, specificity, PPV, NPV, and diagnostic accuracy were 78%, 42.9%, 20%, 91.3%, and 48.3% for predicting the survival of diabetic patients with COVID-19 pneumonia-related myocarditis. Conclusion: This study found that ALT/AST ratio is not a strong predictor of mortality in diabetic patients with COVID-19-related myocarditis.